Tamm Review: Deep fine roots in forest ecosystems: Why dig deeper? - Germon, Amandine [UNESP]; Laclau, Jean-Paul [UNESP]; Robin, Agnès; Jourdan, Christophe (Elsevier, 2020)
While the number of studies dealing with fine root dynamics in deep soils layers (depth > 1 m) has increased sharply recently, the phenology, the morphology, the anatomy and the role of deep fine roots are still poorly known in forest ecosystems. This review summarizes the current knowledge on fine root production, mortality and longevity in deep soil layers, mycorrhizal association with deep roots, and the role of deep fine roots on carbon, water and nutrient cycling in forest ecosystems. Plant species are known to be more deeply rooted in tropical ecosystems than in temperate and boreal ecosystems, but deep-rooted species are common in a wide range of climates. Deep fine roots are highly plastic in response to changes in environmental conditions and soil resources. Recent studies show that functional traits can be different for deep and shallow roots, with a possible functional specialization of deep fine roots to take up nutrients. With higher vessel diameter and larger tracheid, the anatomy of deep fine roots is also oriented toward water acquisition and transport by increasing the hydraulic conductivity. Deep fine roots can have a great impact on the biogeochemical cycles in many forests (in particular in tropical areas where highly weathered soils are commonly very deep), making it possible to take up water and nutrients over dry periods and contributing to store carbon in the soil. The biogeochemical models in forest ecosystems need to consider the specificity of deep root functioning to better predict carbon, water and nutrient cycling as well as net ecosystem productivity.
Keywords: Carbon sequestration; Deep mycorrhizas; Deep rooting; Nutrient uptake; Root growth; Root traits; Water uptake